Changing the shape of ZnO nanostructures by controling Zn vapor release - Ta, Canh Dinh; Tran, Hoa Thi Quynh; Dao, Duy Quang; Nguyen, Tuyen Viet; Nguyen, Hoa Quang; Nguyen, Long Ngoc (VNU Journal of Science: Mathematics - Physics, 2017)
Abstracts